Comparative study on the performance of bentonite, kenaf and zeolite to reduce earth resistance of grounding systems - Lai, Wai Luen (2018)
Grounding systems are designed to dissipate high magnitude fault current to earth and provide safety to persons working in or living near power system installations. It is also necessary that grounding systems are designed with lowmagnitude earth impedance path so that the high magnitude and fast transient surges are dissipated to earth as fast as possible. Therefore, the performance of the grounding system must be in a top-notch condition as it governs the efficiency of the grounding system itself. Based on the local and international grounding standards, it recommended a minimum value of earth resistance need to be achieved for the grounding system to reach a top-notch condition. However, it is difficult to reach low earth resistance in ordinary soil condition as there are variation of soil resistivity from one place to another. Hence, the main objective of this study is to investigate the performance of natural enhancement materials in reducing the earth resistance of the installed grounding systems. The experimental investigations on earth rod grounding system based on soil enhancement was carried out at the site located nearby School of Graduate Studies, UPM, Serdang, Selangor. This experiment was implemented by drilling thirteen cylindrical hollow hole with dimension of 0.13m diameter and 1.5m depth which were each of them filled with different ratio of natural enhancement materials, i.e. Bentonite, Kenaf and Zeolite. After that, thirteen of solid copper earth rod were driven into the centre of each cylindrical hollow hole to a depth of 1.4m. Also, there was another earth rod which was installed without any enhancement material around for comparison purposes. All the copper earth rods utilized were in the similar dimension of 0.013m diameter and 1.5m length. Note that, for all 14 grounding systems, the earth rod is only driven up to the depth of 1.4m with 0.1m allowance for earth resistance measurement purposes. At last, the concrete earth chambers were placed on all the installed grounding systems. Earth resistance measurement was conducted using a 3 point fall of potential method on daily basis for a period of one year. Over a year, the results of earth resistance measurements indicated that the best performed grounding system was Bentonite installation with highest reduction of earth resistance of 76% compared to the reference grounding system at day-0. While, for the worst performed grounding system, it was the mixture of Kenaf and Zeolite installation (with ratio of 30:70) with percentage of increment of earth resistance of 13% when compare with the reference grounding system at day-0. Furthermore, from the results, it is discovered that the increase of the amount of Kenaf or Zeolite used in the mixture of natural enhancement material for grounding system can leads to a reduction of earth resistance but much less effective compared to increase the amount of Bentonite used. The results also shows that Zeolite and Kenaf were not suitable to be used individually or mixed together as they present a poor performance. In conclusion, this study proves that Bentonite are still a better choice as an individual or mixed material for reduction of earth resistance compared to Kenaf and Zeolite.